Stock Option Grants And Cost Behavior - Kwon, Dae-Hyun (Journal of Applied Business Research, 2018)
This study examines the relation between cost asymmetry and stock option grants. I posit that managers’ incentives to decrease the strike price of subsequent option awards may affect manager’s resource adjustment decisions. Using U.S. firm data, I find that the degree of SG&A (selling, general, and administrative) cost asymmetry is positively related to the value of subsequent option grants awarded to the CEOs, suggesting that managers who expect large stock-option grants deliberately delay reduction of committed costs to decrease the share price prior to the option award date. Manipulating the timing of stock option grants do not fully explain the results because the positive relation that this paper documents still holds with only fixed-date option awards sample.
Keywords: Stock Option; CEO Compensation; Resource Adjustment; Cost Behavior